2020
DOI: 10.1177/0020872820930265
|View full text |Cite
|
Sign up to set email alerts
|

Incentive-based Social Welfare Administration in Indonesia: Implications for sustainable development in women’s and children’s protection

Abstract: This article brings together two discrete studies of Indonesian welfare innovations, the conditional cash transfer and the deinstitutionalisation of children, both delivered at the lowest administrative level by social workers. Patterns across the two studies indicated a confounding variable influential in social workers’ innovation implementation and administrative decisions. This variable, incentive-based remuneration, was inhibiting implementation and potentially sustaining the social inequalities and right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Most existing studies reported that leakage is a problem related to program design (Barca, 2017; Sumarto et al, 2007; Yuda et al, 2021) and its implementation (Hossain et al, 2012; McLaren et al, 2020). Neo-institutional framework applied here additionally provides a broader view by presenting an understanding beyond the technical and managerial issues of the programs and also the linkage between various elements leading to the current problem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most existing studies reported that leakage is a problem related to program design (Barca, 2017; Sumarto et al, 2007; Yuda et al, 2021) and its implementation (Hossain et al, 2012; McLaren et al, 2020). Neo-institutional framework applied here additionally provides a broader view by presenting an understanding beyond the technical and managerial issues of the programs and also the linkage between various elements leading to the current problem.…”
Section: Discussionmentioning
confidence: 99%
“…They are designed to target every eligible household; unfortunately, the problems associated with the distribution process usually emerge during the implementation. The limited bureaucratic capacity causes these programs to suffer from weak administration (Barca, 2017; McLaren et al, 2020), transparency, and quality service (Aspinall, 2014). Preliminary studies stated that the capacity to acquire information to identify eligible households is a prerequisite for accurate distribution.…”
Section: Neo-institutionalism Approach For Social Protection Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stunting is one of the targets of the Sustainable Development Goals (SDGs), which are included in sustainable development goals (Heidkamp et al, 2021). The program aims to eliminate hunger and all forms of malnutrition by 2030 and achieve food security to achieve social equality (Arora & Mishra, 2022;McLaren et al, 2022). The target is to reduce the stunting rate by 40% by 2025 (Dake et al, 2019;Quamme & Iversen, 2022).…”
Section: Impact Of the Non-cash Food Assistance Program (Bantuan Pang...mentioning
confidence: 99%
“…Along with increasing awareness of the importance of improving people's welfare(Spoann et al, 2019), Extensive monitoring is also in place to ensure that information is open and transparent when implementing initiatives to reduce poverty(Matheus & Janssen, 2019). It aims to promote adopting policies that ensure sustainable development(Matheus & Janssen, 2019) and welfare innovation in Indonesia(McLaren et al, 2022). In implementing a policy or a program, it is necessary to have an executor responsible for managing the program.…”
mentioning
confidence: 99%